A calculus problem by Rocco Dalto

Calculus Level 3

{ d x d t = 3 x + 2 y + 4 z d y d t = 2 x + 2 z d z d t = 4 x + 2 y + 3 z \begin{cases} \dfrac{dx}{dt} = 3x + 2y + 4z \\ \dfrac{dy}{dt} = 2x + 2z \\ \dfrac{dz}{dt} = 4x + 2y + 3z \end{cases}

The general solution to the above differential system is as follows:

{ x ( t ) = c 1 x 1 ( t ) + c 2 x 2 ( t ) + c 3 x 3 ( t ) y ( t ) = c 1 y 1 ( t ) + c 2 y 2 ( t ) + c 3 y 3 ( t ) z ( t ) = c 1 z 1 ( t ) + c 2 z 2 ( t ) + c 3 z 3 ( t ) \begin{cases} x(t) = c_{1}x_{1}(t) + c_{2}x_{2}(t) + c_{3}x_{3}(t) \\ y(t) = c_{1}y_{1}(t) + c_{2} y_{2}(t) + c_{3}y_{3}(t) \\ z(t) = c_{1}z_{1}(t) + c_{2}z_{2}(t) + c_{3}z_{3}(t) \end{cases} where x j ( t ) y j ( t ) z j ( t ) = v j e λ j t \begin{vmatrix}{x_{j}(t)} \\{y_{j}(t)} \\ {z_{j}(t)} \\ \end{vmatrix} = \vec{v_{j}}* e^{\lambda_{j} t}

for ( 1 < = j < = 3 ) (1 <= j <= 3)

Let

v 1 = A 1 B 1 2 \vec{v_{1}} = \begin{vmatrix}{A_{1}} \\{B_{1}} \\ 2 \\ \end{vmatrix}

v 2 = 1 B 2 0 \vec{v_{2}} = \begin{vmatrix}{1} \\{B_{2}} \\ 0 \\ \end{vmatrix}

v 3 = 0 B 2 1 \vec{v_{3}} = \begin{vmatrix}{0} \\{B_{2}} \\ 1 \\ \end{vmatrix} .

If x ( 0 ) = 0 x(0) = 0 , y ( 0 ) = 1 y(0) = 1 , and z ( 0 ) = 2 z(0) = 2 and c 1 + c 2 + c 3 = a b c_{1} + c_{2} + c_{3} = \dfrac{a}{b} , where a a and b b are coprime positive integers,

Find: a + b a + b .

H i n t : Hint: The eigenvalues are λ 1 R \lambda_{1} \in \mathbb{R} with Eigenvector v 1 \vec{v_{1}} and λ 2 = λ 3 R \lambda_{2} = \lambda_{3} \in \mathbb{R} with two Linear Independent Eigenvectors v 2 \vec{v_{2}} and v 3 \vec{v_{3}} .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rocco Dalto
May 19, 2017

Let x ( t ) = A e λ t x(t) = A * e^{\lambda t} y ( t ) = B e λ t y(t) = B * e^{\lambda t} z ( t ) = C e λ t z(t) = C * e^{\lambda t}

d x d t = λ A e λ t , d y d t = λ B e λ t , d x d t = λ C e λ t \implies \dfrac{dx}{dt} = \lambda * A * e^{\lambda t}, \: \dfrac{dy}{dt} = \lambda * B * e^{\lambda t}, \: \dfrac{dx}{dt} = \lambda * C * e^{\lambda t}

Replacing the above in the differential system we obtain the system:

[ 3 λ 2 4 2 λ 2 4 2 3 λ ] A B C = 0 0 0 \begin{bmatrix}{3 - \lambda} && {2} && {4}\\ {2} && {- \lambda} && {2}\\ {4} && {2} && {3 - \lambda} \end{bmatrix} * \begin{vmatrix}{A} \\{B} \\ {C} \\ \end{vmatrix} = \begin{vmatrix}{0} \\{0} \\ {0} \\ \end{vmatrix}

We want a nontrivial solution so let det ( [ 3 λ 2 4 2 λ 2 4 2 3 λ ] ) = 0 \det(\begin{bmatrix}{3 - \lambda} && {2} && {4}\\ {2} && {- \lambda} && {2}\\ {4} && {2} && {3 - \lambda} \end{bmatrix}) = 0

( λ + 1 ) 2 ( 8 λ ) = 0 λ = 1 , λ = 8 \implies (\lambda + 1)^2 * (8 - \lambda) = 0 \implies \lambda = -1, \: \lambda = 8

For λ = 8 \lambda = 8 we obtain the system:

[ 5 2 4 0 2 8 2 0 4 2 5 0 ] \left[ \begin{array}{ccc|c} -5 & 2 & 4 & 0\\ 2 & -8 & 2 & 0\\ 4 & 2 & -5 & 0 \\ \ \end{array} \right]

Using row operations we obtain:

[ 1 4 1 0 0 2 1 0 0 0 0 0 ] \left[ \begin{array}{ccc|c} 1 & -4 & 1 & 0\\ 0 & -2 & 1 & 0\\ 0 & 0 & 0 & 0 \\ \ \end{array} \right]

\implies

A 1 4 B 1 + C 1 = 0 A{1} - 4 B_{1} + C_{1} = 0 2 B 1 + C 1 = 0 -2 B_{1} + C_{1} = 0

Let C 1 = 2 B 1 = 1 A 1 = 2 C_{1} = 2 \implies B_{1} = 1 \implies A_{1} = 2

v 1 = 2 1 2 \vec{v_{1}} = \begin{vmatrix}{2} \\{1} \\ {2} \\ \end{vmatrix}

For λ = 1 \lambda = -1 we obtain:

[ 4 2 4 0 2 1 2 0 4 2 4 0 ] \left[ \begin{array}{ccc|c} 4 & 2 & 4 & 0\\ 2 & 1 & 2 & 0\\ 4 & 2 & 4 & 0 \\ \ \end{array} \right]

Using row operations we obtain:

[ 4 2 4 0 0 0 0 0 0 0 0 0 ] \left[ \begin{array}{ccc|c} 4 & 2 & 4 & 0\\ 0 & 0 & 0 & 0\\ 0 & 0 & 0 & 0 \\ \ \end{array} \right]

\implies

2 A 2 + B 2 + 2 C 2 = 0 2 A_{2} +B_{2} + 2 C_{2} = 0

We have two degrees of freedom so let A 2 A_{2} and C 2 C_{2} be arbitrary variables B 2 = 2 A 2 2 C 2 \implies B_{2} = -2 A{2} - 2 C_{2} .

For A 2 = 1 , C 2 = 0 B 2 = 2 A_{2} = 1, \: C_{2} = 0 \implies B_{2} = -2 and v 2 = 1 2 0 \vec{v_{2}} = \begin{vmatrix}{1} \\{-2} \\ {0} \\ \end{vmatrix}

For A 2 = 0 , C 2 = 1 B 2 = 2 A_{2} = 0, \: C_{2} = 1 \implies B_{2} = -2 and v 3 = 0 2 1 \vec{v_{3}} = \begin{vmatrix}{0} \\{-2} \\ {1} \\ \end{vmatrix}

Every solution has the form:

A 2 B 2 C 2 = A 2 1 2 0 + C 2 0 2 1 \begin{vmatrix}{A_{2}} \\{B_{2}} \\ {C_{2}} \\ \end{vmatrix} = A_{2} \begin{vmatrix}{1} \\{-2} \\ {0} \\ \end{vmatrix} + C_{2} \begin{vmatrix}{0} \\{-2} \\ {1} \\ \end{vmatrix}

\therefore The general solution is:

x ( t ) = 2 c 1 e 8 t + c 2 e t x(t) = 2 c_{1} e^{8t} + c_{2} e^{-t} y ( t ) = c 1 e 8 t 2 c 2 e t 2 c 3 e t y(t) = c_{1} e^{8t} - 2 c_{2} e^{-t} - 2 c_{3} e^{-t} z ( t ) = 2 c 1 e 8 t + c 3 e t z(t) = 2 c_{1} e^{8t} + c_{3} e^{-t}

x ( 0 ) = 0 x(0) = 0 , y ( 0 ) = 1 y(0) = 1 , and z ( 0 ) = 2 z(0) = 2 \implies

( 1 ) : 2 c 1 + c 2 = 0 (1): 2 c_{1} + c_{2} = 0 ( 2 ) : c 1 2 c 2 2 c 3 = 1 (2): c_{1} - 2 c_{2} - 2 c_{3} = 1 ( 3 ) : 2 c 1 + c 3 = 2 (3): 2 c_{1} + c_{3} = 2

Multiplying equation ( 1 ) (1) by 2 2 and adding to equation ( 2 ) (2) we obtain:

5 c 1 2 c 3 = 1 5 c_{1} - 2 c_{3} = 1 2 c 1 + c 3 = 2 2 c_{1} + c_{3} = 2

c 1 = 5 9 c 3 = 8 9 c 2 = 10 9 c 1 + c 2 + c 2 = 3 9 = 1 3 = a b \implies c_{1} = \dfrac{5}{9} \implies c_{3} = \dfrac{8}{9} \implies c_{2} = \dfrac{-10}{9} \implies c_{1} + c_{2} + c_{2} = \dfrac{3}{9} = \dfrac{1}{3} = \dfrac{a}{b}

a + b = 4 \implies a + b = \boxed{4} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...